KEPEMIMPINAN TRANSFORMASIONAL DALAM MENINGKATKAN KINERJA GURU - Subhan Fadli; Yunus Yunus (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2023)
Abstract: This research is motivated by the low performance of teachers in an educational institution. This was caused by the leadership of the principal who did not play a role. The role of transformational leadership has an impact on good teacher performance, it turns out that it is dominated by a liking for leadership, so that they feel comfortable at work. Therefore, this study aims to explain the role of transformational leadership of school principals in improving the performance of teachers at the Shohifatusshofa Rawamangun Islamic Boarding School and to determine the role of transformational leadership of school principals in improving teacher performance at the Shohifatusshofa Islamic Boarding School Rawamangun. In addition, good teacher performance is also influenced by continuous and consistent rewards and punishments from superiors to subordinates, so that teachers who are really creative and good feel valued and teachers whose performance is not good feel constantly supervised.Keywords: transformational leadership; teacher performance; islamic boarding schools Abstrak: Penelitian ini dilatarbelakangi oleh kinerja guru yang rendah pada sebuah lembaga pendidikan. Hal itu disebabkan oleh kepemimpinan kepala sekolah yang kurang berperan. Peran kepemimpinan transformasional berdampak kinerja guru yang baik ternyata didominasi oleh rasa suka terhadap kememimpin, sehingga mereka merasa nyaman dalam bekerja. Penelitian ini bertujuan untuk menjelaskan peran kepemimpinan transformasional kepala sekolah dalam meningkatkan kinerja guru Pesantren Shohifatusshofa Rawamangun dan untuk mengetahui peran kepemimpinan transformasional kepala sekolah dalam meningkatkan kinerja guru di Pesantren Shohifatusshofa Rawamangun. Di samping itu, performa kinerja guru yang baik tersebut juga dipengaruhi oleh adanya reward dan punishment dari atasan ke bawahan dengan continue dan konsisten, sehingga guru yang benar-benar kreatif dan baik merasa dihargai dan guru yang kinerjanya kurang bagus merasa terus terawasi.Kata kunci: kepemimpinan transformasional; kinerja guru; pesantren